Photoelectron Circular Dichroism of Bicyclic Ketones from Multiphoton Ionization with Femtosecond Laser Pulses. Issue 1 (9th December 2014) - Lux, Christian; Wollenhaupt, Matthias; Sarpe, Cristian; Baumert, Thomas
Abstract Photoelectron circular dichroism (PECD) is a CD effect up to the ten‐percent regime and shows contributions from higher‐order Legendre polynomials when multiphoton ionization is compared to single‐photon ionization. We give a full account of our experimental methodology for measuring the multiphoton PECD and derive quantitative measures that we apply on camphor, fenchone and norcamphor. Different modulations and amplitudes of the contributing Legendre polynomials are observed despite the similarity in chemical structure. In addition, we study PECD for elliptically polarized light employing tomographic reconstruction methods. Intensity studies reveal dissociative ionization as the origin of the observed PECD effect, whereas ionization of the intermediate resonance is dominating the signal. As a perspective, we suggest to make use of our tomographic data as an experimental basis for a complete photoionization experiment and give a prospect of PECD as an analytic tool.